2012
DOI: 10.1177/1464419311430176
|View full text |Cite
|
Sign up to set email alerts
|

Predictive capabilities of the MADYMO multibody pedestrian model: Three-dimensional head translation and rotation, head impact time and head impact velocity

Abstract: Road traffic injuries could become the fifth leading cause of death globally by 2030 unless appropriate countermeasures are taken. Reliable reconstruction of collisions is essential for understanding and hence reducing the injuries sustained by pedestrians. The significant influence of vehicle speed, pedestrian speed and pedestrian gait on pedestrian transverse motion and rotation about the longitudinal axis has been qualitatively noted in the literature, but there has been no quantitative approach to this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Both models were compared to the 10% pathlength corridors of PMHS tests developed by Kerrigan et al (2005) showed an error between 1% and 36% in head impact velocity between the model and PMHS (Elliott et al, 2012a;van Hoof et al, 2003). Further evaluation of both models is needed by also including the rotation and displacement in the xy-plane.…”
Section: Difference In Head Kinematics Between the Two Modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Both models were compared to the 10% pathlength corridors of PMHS tests developed by Kerrigan et al (2005) showed an error between 1% and 36% in head impact velocity between the model and PMHS (Elliott et al, 2012a;van Hoof et al, 2003). Further evaluation of both models is needed by also including the rotation and displacement in the xy-plane.…”
Section: Difference In Head Kinematics Between the Two Modelsmentioning
confidence: 97%
“…Mottola et al (2013) (Alvarez et al 2013;Hedenstierna and Halldin 2008;Kleiven 2007). Both models have previously been compared to experimental tests on both component and full-body level (Elliott et al 2012a;van Hoof et al 2003;Maeno and Hasegawa 2001;Tamura et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…M A DYMO software for the pedestrian kinematics and Finites Elements simulation for the Hybrid head impact against the windscreen can be used for conduction (Elliott et al, 2012).…”
Section: Fig 2 Risk Of Pedestrian Death As a Function Of Vehicle Immentioning
confidence: 99%
“…They noted that spine and neck stiffness appeared to change the upper body and head kinematics, and that sliding over the bonnet appeared to increase head velocity towards the vehicle. Elliott et al [4] simulated 14 PMHS tests, 7 dummy tests and a real-world collision with a multibody HBM.…”
Section: Introductionmentioning
confidence: 99%